Performance of Composite Shear Walls Subjected to In-plane Cyclic Loading - A Numerical Parametric Study - Labibzadeh, Mojtaba; Salehnia, Anis; Hossain, Khandaker M. A.; Jing, Deng-Hu (Periodica Polytechnica Civil Engineering, 2021)
An RC shear wall (wall1), a composite shear wall composed of a single external steel plate connected to a concrete panel (wall2), a composite shear wall constructed from two external steel plates connected to an internal concrete panel (wall3) and finally a composite shear wall fabricated with a single internal steel plate embedded within a concrete panel (wall4) are considered in this study and their behavior are assessed and compared under the effect of an in-plane cyclic load. Variation of the three functions include shear load capacity, energy absorption and shear stiffness of the walls are evaluated numerically using the ABAQUS finite element software. The performance of numerical models is validated against to the experimental results. The effects of four parameters consisting of compressive strength of concrete, yield strength of steel plate, height-to-length ratio of the wall and the thickness of the steel plate are investigated on the above-mentioned functions. Obtained results show that the wall4 has the best performance among all four types of shear walls. For instance, the energy absorption capacity of the wall4 is approximately two times greater than that of wall1 and wall2.